Evaluation of Ba0.6Sr0.4Co0.9Nb0.1O3-d mixed conductor as a cathode for intermediate-temperature oxygen-ionic solid-oxide fuel cells - Huang, C.; Chen, D.; Lin, Y.; Ran, R.; Shao, Zongping (Elsevier SA, 2010)
A perovskite-type Ba0.6Sr0.4Co0.9Nb0.1O3-d (BSCN) oxide is investigated as the cathode material of oxygen-ionic solid-oxide fuel cells (SOFCs) with Sm0.2Ce0.8O3-d (SDC) electrolyte. Powder X-ray diffraction and SEM characterization demonstrate that solid phase reactions between BSCN and SDC are negligible at temperatures up to 1100 °C. The results of thermal-expansion and electrical conductivity measurements indicate the introduction of Ba2+ into the A-site of SrCo0.9N0.1O3-d (SCN) led to a decrease in the thermal-expansion coefficient (TEC) and electrical conductivity of the compound. A TEC of 14.4 × 10-6 K-1 is observed for BSCN within a temperature range of 200-500 °C. The chemical diffusion coefficient (Dchem) and surface exchange constant (kex) of BSCN and SCN are obtained using an electrical conductivity relaxation technique and BSCN prove to have higher Dchem and kex than SCN. An area-specific resistance of 0.1 O cm-2 is achieved for BSCN cathodes at 600 °C based on symmetric cells test. Peak power density of ~1150 mW cm-2 is reached for a thin-film electrolyte cell with BSCN cathode at 600 °C, which is higher than a similar cell with SCN cathode (~1008 mW cm-2). BSCN is a promising cathode material for oxygen-ionic IT-SOFCs. © 2010 Elsevier B.V. All rights reserved.